Hubungan Body Dissatisfaction dengan Social Anxiety pada Mahasiswi Fakultas Psikologi Universitas “X” Angkatan 2018 - Miryam Ariadne Sigarlaki; Dhiya Dzahabiyyah (Humanitas (Jurnal Psikologi), 2022)
This research aims to find out the corellation between body dissatisfaction and social anxiety among female students in Faculty of Psychology from “X” University Class of 2018. The sample size is 42 female students, selected by accidental sampling technique. “The Multidimensional Body-Self Relations Questionnaire-Appearance (MBSRQ-AS)” used to measure the body dissatisfaction and “Liebowitz Social Anxiety Scale” for social anxiety. Researcher used spearman correlation test to analyze the data. The result show that there is a correlation between body dissatisfaction and social anxiety among female students in Faculty of Psychology from “X” University Class of 2018 (spearman rho 0.708*** with p value = <0.001). The higher the body dissatisfaction that sample get, the higher level of social anxiety is. Suggestions from researchers, this study can be used as reference material for information to be socialized among female students about body dissatisfaction related to social anxiety.